The Potential of Silk and Silk-Like Proteins as Natural Mucoadhesive Biopolymers for Controlled Drug Delivery - Brooks, Amanda E. (Frontiers in Chemistry, 2015)
Drug delivery across mucus membranes is a particularly effective route of administration due to the large surface area. However, the unique environment present at the mucosa necessitates altered drug formulations designed to (1) deliver sensitive biologic molecules, (2) promote intimate contact between the mucosa and the drug, and (3) prolong the drug’s local residence time. Thus, the pharmaceutical industry has an interest in drug delivery systems formulated around the use of mucoadhesive polymers. Mucoadhesive polymers, both synthetic and biological, have a history of use in local drug delivery. Prominently featured in the literature are chitosan, alginate, and cellulose derivatives. More recently, silk and silk-like derivatives have been explored for their potential as mucoadhesive polymers. Both silkworms and spiders produce sticky silk-like glue substances, sericin and aggregate silk respectively, that may prove an effective, natural matrix for drug delivery to the mucosa. This mini review will explore the potential of silk and silk-like derivatives as a biocompatible mucoadhesive polymer matrix for local controlled drug delivery.